Perception and Practice about Menstrual Health/Hygiene Among Adolescent Girls in Barisal District - Shelley, Farida Easmin (Ibrahim Cardiac Medical Journal, 2022)
Background & Objective: Although menstruation is a natural physiological process and usually goes away without any complex problems provided proper care is taken during the period. However, menstruation is linked with religious and cultural meanings that can affect the perceptions of young girls and the ways in which the adult communities around them respond to their felt-needs. So, menstruation-associated complaints are not uncommon. The present study was, therefore, intended to determine the perception and practice of adolescent girls about menstruation in Barisal District. Methods: This cross-sectional descriptive study was conducted as part of Field-site Survey of the Department of Social Science & Public Health (SSPH). Having obtained consent from the parents/guardians, a total of 205 adolescent girls from the Barisal district (both from Barisal Metropolitan City and rural area of the District) who had experienced menarche at least 6 months prior to the day of interview were included in the study. Data were collected over a period of three months from July 2020 to September 2020. Before interview, the issue of menstruation was discussed with the respondents. The interview was done by the female Health Assistants (field staff of Upalzila Health Complex in the Government setting) so that the interviewees answer freely to such private matters as menstruation thereby reducing the chance of bias during interview. Result: Nearly 70% of the respondents were 14-16 years old with mean age of the girls being 15.2 ± 1.6 years. Majority of the respondents was unmarried (95.1%), urban resident (86.8%) and students of Public-School (66.8%). In terms of socioeconomic status, almost half (49.3%) was middle class, 29.8% lower middle class and 10.7% upper middle class. Most (87.8%) of the respondents had their menarche at 11-14 years with mean age at menarche being 12.9 ± 1.3 years. Over two-thirds (68.8%) of the respondents reported their length of menstrual cycle to vary from 26 – 30 days and period to vary from 3-5 days. A substantial proportion (83.4%) of respondents had regular menstruation. The predominant complaint during menstruation was fatigue or tiredness (73.2%) followed by pelvic pain (62%), malaise (60%) and low back pain (38.5%). Over half (50.4%) consulted with physicians, 11.8% with drug-sellers, 3.9% with herbal healer and 1.6% with homeopath for pain relief. Approximately 57% took analgesics to get relief from the pain. Other symptoms or complaints relating to menstruation were altered appetite (55.6%), abdominal bloating (39%), heavy bleeding (45.4%) and frequency of micturition (31.7%). About 46% of the respondents’ routine activities were adversely affected, social relationships disrupted (32.7%), family relationship hampered (25.4%), sports/exercise activities stopped or reduced (58%). Nearly half (47.8%) of them had to absent from the school during the period with average school absenteeism of 3-4 days each month being reported by more than half of the cases. Majority (94.6%) of the respondents perceived that ‘period of adolescent girls’ should occur every month and that their period should not make them anxious (81.5%). About 83% told that a period of 3-5 days duration be considered normal. Almost 94% took some sanitary measures while they were on period. Majority (87.3%) talked the issue to a family member and about 64% to friends. Over one-third (37.6%) sought suggestion about menstrual affairs from their mothers, 27.8% from their sisters, 26.8% from friends and relations and only 7.8% from doctors. Conclusion: Majority of the adolescent girls start menstruation at 11-14 years with mean age at menarche being 13 years. Adolescent girls usually adopt hygienic measures during the period by using sanitary napkin or clean home-made pad. The predominant symptoms experienced during the period are pelvic pain, malaise and low back pain. Other symptoms are loss of appetite, flatulence, heavy bleeding and frequency of micturition with personal, familial and social life being adversely affected and they remain absent from the school during the period in each cycle. Half of the girls consult with physicians for pain relief and take analgesics. Ibrahim Card Med J 2021; 11 (1): 79-85